2010
DOI: 10.1111/j.1471-6712.2009.00718.x
|View full text |Cite
|
Sign up to set email alerts
|

‘We got the whole story all at once’: physiotherapists’ use of key questions when meeting patients with long‐standing pain

Abstract: Long-standing musculoskeletal pain has many dimensions. Physiotherapy lacks a tested method of dialogue with which physiotherapists and patients can together explore pain in all its complexity. The present aim was to find out how physiotherapists experienced the influence of systematically prepared key questioning on their relation to, and understanding of, patients with long-standing pain. A group of six physiotherapists with long experience of pain rehabilitation used such questions in their encounters with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
6
0
1
Order By: Relevance
“…The themes are drawn from a wide range of HCPs, including those specialising in chronic pain management who may be more likely to adopt a biopsychosocial approach. 146 147 155 157 164 185 198 199 211 212 215 217 219 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The themes are drawn from a wide range of HCPs, including those specialising in chronic pain management who may be more likely to adopt a biopsychosocial approach. 146 147 155 157 164 185 198 199 211 212 215 217 219 …”
Section: Resultsmentioning
confidence: 99%
“…If you start from the body and if you ask a little carefully how things work when you are physically like that, then it is not threatening, and you can approach things, like, through the body. 146 (Afrell, 2010, pain specialist, physiotherapist, Norway)…”
Section: Resultsmentioning
confidence: 99%
“…She found that the dialogue started a process of change and it is possible to discuss these types of issues with patients, but physiotherapists need support in order to take up such topics. This was a matter of uncertainly about the professional role or mandate of physioterapist (Afrell & Rudebeck, 2010).…”
Section: Body Awareness As a Resource For Healthmentioning
confidence: 99%
“…Many health care researchers with a professional background in somatic care are astonished initially at the interventional power their interviews seem to have when they are performing a qualitative study addressing a patient group. One of them is the Swedish physiotherapist Maria Afrell who, whilst exploring patients’ experiences of “living with a body in pain”, found that her method of asking questions had interventional power 21,22. In our study, the patients’ descriptions indicate that the narrative approach taken by the consultant team might have been key to the success of the intervention.…”
Section: Discussionmentioning
confidence: 66%